Influence of Leadership and Work Discipline on Employee Performance at The Department of Population and Civil Registration, City of Cirebon - Soleman, Soleman; Setiadi, Ade; Sugiyarsih, Susi (Universitas Negeri Semarang, 2025)
This study aims to analyze the influence of supervision on employee work discipline at the Department of Housing, Settlement Areas, and Land Affairs of Cirebon Regency. Supervision is defined as an organizational control mechanism consisting of direct and indirect supervision, while work discipline includes preventive and corrective discipline. This research employed a quantitative approach using a saturated sampling technique, involving all 79 employees as respondents. Data were collected through questionnaires and analyzed using descriptive statistics and simple linear regression. The results indicate that the level of supervision is categorized as “good,” with an average score of 3.70, while employee work discipline is categorized as “high,” with an average score of 3.85. The regression analysis confirms that supervision has a positive and significant influence on employee discipline. These findings highlight that strengthening supervision—both direct and indirect—plays a crucial role in improving employee discipline. The study contributes to the development of internal supervision policies for local government agencies.